Sea Trials of a Prototype of a Deep-Sea Tide Guague - Dupuy, P. Y. (The International Hydrographic Review, 2015)
In 1991, SHOM carried out trials, at sea, of a prototype deep-sea tide gauge. The trials made it possible to verify the appropriateness of a known drift model applied to the response from the PAROSCIENTTFIC pressure sensor which was fit into the prototype and to show the instrument’s possibilities studies of tide and mean sea level.